A thermophilic cell-free cascade enzymatic reaction for acetoin synthesis from pyruvate - Xiaojing Jia (Nature Portfolio, 2017)
Abstract Acetoin (3-hydroxy-2-butanone) is an important bio-based platform chemical with wide applications. In vitro enzyme catalysed synthesis exhibits great feasibility in the production of chemicals with high purity. In the present work, a synthetic pathway involving a two-step continuous reaction was constructed in vitro for acetoin production from pyruvate at improved temperature. Thermostable candidates, acetolactate synthase (coAHASL1 and coAHASL2 from Caldicellulosiruptor owensensis OL) and α-acetolactate decarboxylase (bsALDC from Bacillus subtilis IPE5-4) were cloned, heterologously expressed, and characterized. All the enzymes showed maximum activities at 65–70 °C and pH of 6.5. Enzyme kinetics analysis showed that coAHASL1 had a higher activity but lower affinity against pyruvate than that of coAHASL2. In addition, the activities of coAHASL1 and bsALDC were promoted by Mn2+ and NADPH. The cascade enzymatic reaction was optimized by using coAHASL1 and bsALDC based on their kinetic properties. Under optimal conditions, a maximum concentration of 3.36 ± 0.26 mM acetoin was produced from 10 mM pyruvate after reaction for 24 h at 65 °C. The productivity of acetoin was 0.14 mM h−1, and the yield was 67.80% compared with the theoretical value. The results confirmed the feasibility of synthesis of acetoin from pyruvate with a cell-free enzyme catalysed system at improved temperature.